Enhanced Production of D-Lactate in Cyanobacteria by Re-Routing Photosynthetic Cyclic and Pseudo-Cyclic Electron Flow - Selão, Tiago Toscano; Jebarani, Jasmin; Ismail, Nurul Aina; Norling, Birgitta; Nixon, Peter Julian (Frontiers in Plant Science, 2020)
Cyanobacteria are promising chassis strains for the photosynthetic production of platform and specialty chemicals from carbon dioxide. Their efficient light harvesting and metabolic flexibility has allowed a wide range of biomolecules, such as the bioplastic polylactate precursor D-lactate, to be produced, though usually at relatively low yields. In order to increase photosynthetic electron flow towards the production of D-lactate, we have generated several strains of the marine cyanobacterium Synechococcus sp. PCC 7002 (Syn7002) with deletions in genes involved in cyclic or pseudo-cyclic electron flow around photosystem I. Using a variant of the Chlamydomonas reinhardtii D-lactate dehydrogenase (LDHSRT, engineered to efficiently utilize NADPH in vivo), we show that deletion of either of the two flavodiiron flv homologues (involved in pseudo-cyclic electron transport) or the Syn7002 pgr5 homologue (proposed to be a vital part of the cyclic electron transport pathway) is able to increase D-lactate production in Syn7002 strains expressing LDHSRT and the Escherichia coli LldP (lactate permease), especially at low temperature (25 °C) and 0.04% (v/v) CO2, though at elevated temperatures (38 °C) and/or high (1%) CO2 concentrations the effect was less obvious. The Δpgr5 background seemed to be particularly beneficial at 25 °C and 0.04% (v/v) CO2, with a nearly 7-fold increase in D-lactate accumulation in comparison to the wild-type background (≈1000 vs ≈150 mg/L) and decreased side effects in comparison to the flv deletion strains. Overall, our results show that manipulation of photosynthetic electron flow is a viable strategy to increase production of platform chemicals in cyanobacteria under ambient conditions.